Futures Price Response to Crop Reports in Grain Markets. Issue 10 (20th November 2015) - Mattos, Fabio L.; Silveira, Rodrigo L. F.
Abstract : The purpose of this study is to investigate the impact of crop reports from U.S. and Brazil on corn and soybean futures markets over the period 2004–2014. A TARCH model with dummy variables to measure the impact of crop reports is used. Results indicate that U.S. reports consistently affect corn and soybean futures price volatility, while Brazilian crop reports' impact on volatility is of smaller magnitude. Further, these impacts are generally found to be stronger when crop reports are released in the months preceding the beginning of harvest. © 2015 Wiley Periodicals, Inc. Jrl Fut Mark 36:923–942, 2016